Vitamin d and leishmaniasis: Neither seasonal nor risk factor in canine host but potential adjuvant treatment through cbd103 expression - Martori, Clara; Velez, Rita; Gállego, Montserrat; Mesa, Ignacio; Ferreira, Rui; Alberola, Jordi; Rodríguez-Cortés, Alhelí (PLOS Neglected Tropical Diseases, 2021)
Author summary Vitamin D (VitD), the precursor of the powerful steroid hormone calcitriol, has been widely known to regulate the calcium and phosphate homeostasis. Several studies have shown that VitD plays also an important role on innate immunity. The mechanisms by which VitD modulates the immune function have been studied within different contexts involving multiple pathogens, but not Leishmania sp. It is known that VitD strengthens the innate immune system by inducing the expression of anti-microbial peptides in Mycobacterium tuberculosis-infected human macrophages. Antimicrobial peptides act on the bacterial wall, increasing the formation of reactive oxygen species, modulating cytokine expression, and inducing autophagy. Immune system plays a key role in leishmaniasis disease control, thus VitD could have a relevant contribution in leishmaniasis. In a previous study, we shown that clinical leishmaniasis is associated with VitD deficiency. This research aims to determine whether vitamin D is seasonal and a risk factor for developing canine leishmaniasis and, also, to study the possible VitD anti-parasitic effect and the expression of genes related to VitD pathway. The results show that VitD in canine leishmaniasis is neither seasonal nor a risk factor for developing clinical disease. However, its role in reducing parasite load suggests that VitD could be an adjuvant in leishmaniasis therapy.